Profile of Regulatory Motivation of Exercise Among Final Year Students Based on the BREQ-2 Instrument - Muhammad Fedrian; Mustika Fitri; Syam Hardwis; Nor Eeza Zainal Abidin; Hilmy Apriady (Universitas Negeri Semarang, 2026)
Background: Physical activity is one of the most important factors in maintaining physical fitness and mental health among students. Sometimes motivation to exercise declines over time among final-year students due to academic responsibilities, focus on completing final assignments, and a new orientation focused on preparing for the world of work. This situation is one of the factors causing a decline in motivation to exercise. Although recent studies have examined the motivation to exercise in the general population, specific studies examining the motivation to exercise among final-year university students are still very limited. In researching their exercise motivation profiles, it is essential to support a sustainable active lifestyle in their college environment. Objectives: This study aims to examine the regulation of exercise motivation among final-year university students based on the Behavioral Regulation in Exercise Questionnaire-2 (BREQ-2) and to investigate the most dominant form of motivation regulation that influences their participation in exercise. Method: This study used a quantitative descriptive design with 35 final-year active students selected through purposive sampling. The BREQ-2 instrument, consisting of 19 items across five motivational dimensions, was administered online. The collected data was analyzed using descriptive statistics to obtain the mean value, minimum value, maximum value, standard deviation, and percentage distribution for each dimension. Result: The findings of this study show low scores of amotivation (M= 2.43) and external regulation (M= 3.46), indicating indifference and minimal influence from external pressures. Introjected regulations was in moderate category (M= 6.40), reflecting a sense of self-imposed obligation. Identified regulation (M= 12.14) and intrinsic motivation (M+ 13.66) scored the highest, indicating that students engage in exercise based on personal value and enjoyement. Conclusion: Overall, the results of the study show a motivation profile dominated by things that arise from and are enjoyed by themselves, especially in identified regulation and intrinsic motivation. However, motivation levels tend to be moderate based on the distribution of scores. The results of this study emphasize the importance of campus efforts in improving opportunities for better and more flexible exercise in order to strengthen sustained participation in sports among final-year students. This study contributes by examining more specific group, namely final-years students, which has not been previously explored in detail or with a specific focus.